Job and life satisfaction: The perspective of collegiate head coaches - Bopp, T.; Wigley, B. J.; Eddosary, M.; Brewer, B.; Hanin, J. (International Journal of Sports Science and Coaching, 2015)
Research regarding the relationship between job and life satisfaction has drawn opposing conclusions, with some suggesting one`s satisfaction with work is significantly and positively related to one`s attitude of life, while others claim the relationship between the two is at best weak. The purpose of this research was to further expand on the relationship between job and life satisfaction among National Collegiate Athletic Association (NCAA) head coaches. To this end, data from 348 head coaches across all three NCAA Divisions were analyzed. Results imply that life satisfaction and job satisfaction are significantly and positively related in the collegiate coaching context. However, the relationship between the two constructs was not reciprocal and the unidirectional effects differed based on the gender of the team coached. Practical implications of these findings might offer significant insights for managers and policy makers such that they are better equipped to establish and increase work (e.g., job) and non-work (e.g., life) satisfaction.